Uso de geotecnologias para o zoneamento ambiental da Sub-bacia Hidrográfica do Rio do Quilombo: subsídios voltados para área de expansão urbana do município de São Carlos – SP - Domingues, João Mateus Marão (2021)
The physical and environmental aspects are constantly forgotten during the planning phase, which is why there is a triggering of environmental risks arising from public management problems. In the scope of municipal planning, the master plan has a fundamental role in defining strategic guidelines for the socioeconomic development of a city. Among the variety of urban tools within a master plan, it is found in the environmental zoning that aims to identify and delimit environmental units according to their physical characteristics and fragilities. The technological advent provided the development of Geographic Information Systems optimizing the processes of territorial planning, and evaluation of the interaction between the anthropic and physical methods. This work aims to support urban planning through the development of environmental zoning inserted in the urban expansion area of São Carlos, in the Hydrographic Sub-basin of Quilombo River. The distinction of environmental zones will be based on the subdivision of the territory according to its potentialities based on physical attributes. The methodological development based on this research has three stages, the first being defined by the diagnosis that has to analyze and structure spatial information; the second stage consists of the prognosis based at processing the information from the previous stage; and the third procedure for the integration and interpretation of the cartographic documents generated. The processing of geospatial data and geoprocessing operations were performed through the use of the QGIS program. To achieve the results, it was necessary to develop five cartographic documents, defined by the maps of altitude, slope, use and occupation of the soil, rocky substrate and unconsolidated material. With the help of map algebra, it was possible to elaborate two environmental zoning maps, estimated by the weighted and simple arithmetic averages. The suitability towards future urban infrastructure implementations in the area studied was classified according to suitability, varying between more or less favorable areas. Despite presenting favorable trends in the urban expansion region of São Carlos, it is seen that the same region is in the macro zone of protection of water sources. The territorial planning and the classifications obtained are fundamental for the management of rational occupation with a view to the sustainable use of the natural resources of the territory.